Chronic early-life social isolation affects NMDA and TrkB receptor expression in a sex-specific manner. (24th August 2021) - Gondora, Nyasha; Pople, Christopher B.; Tandon, Gorvie; Robinson, Morgan; Solomon, Eden; Beazely, Michael A.; Mielke, John G.
Highlights: Chronic early-life social isolation (CELSI) uniquely alters plasticity proteins. CELSI increases TrkB expression in the HP and PFC of male, but not female, rats. CELSI increases GluN2B expression in the HP and PFC of male, but not female, rats. Abstract: Exposing mammals to adverse social environments early in life can affect brain development in ways that alter adult behaviour. For example, chronic, early-life social isolation (CELSI) has been found to cause novelty-induced hyperactivity, impaired pre-pulse inhibition, and enhanced anxiety-related behaviour. Although the molecular mechanism(s) underlying the embedding of CELSI have not been fully elucidated, evidence suggests changes in the level of excitatory neurotransmission and neurotrophic factor signalling may be quite important. Since much of the work in this area has focused upon mRNA-level analyses, and has shown variable responses across both brain region and animal sex, our study aimed to explore the impact of CELSI on the expression of two important plasticity-related proteins (Tropomyosin receptor kinase B and the GluN2B subunit of the NMDA receptor) in the pre-frontal cortex and hippocampus of both male and female rats. We observed that the expression of both proteins was clearly changed by CELSI, but that the effect occurred in a sex (but not region) specific manner. Our results support the growing view that early-life adversity can cause structural changes reasonably associated with adult behaviour, and emphasise that the study of such changes benefits from a sex-based analysis.